Sistemas de manejo de colheita mecanizada da canola - Pizolotto, Carlos Augusto (2015)
Canola (Brassica napus L. var. oleifera) is an oilseed species belonging to the Brassicacea with the potential for broad use in grain production systems in Southern Brazil. However, the culture has some factors that hinder its installation and field management, including the uneven ripening of seedpods, which feature natural dehiscence, causing excessive grain losses during ripening and harvesting times. This study aimed to evaluate and compare different canola crop management systems, to reduce crop losses and consequently obtain higher grain yield. In 2013 and 2014, five experiments were conducted at the experimental field of the Faculdade de Agronomia e Medicina Veterinária in the Universidade de Passo Fundo (FAMV/UPF), with the canola hybrid Hyola 61 and the open-pollinated cultivar ALHT 1000. Crop management systems used were conducted with or without the application of the sealant Grip®, and were the following: cut-windrowing, previous chemical desiccation with diquat or glufosinate ammonium, ethephon application and harvest with direct cutting at the natural point of maturation. The harvest management with cut-windrowing or with previous chemical desiccation are the management alternatives that significantly reduce crop losses and allow higher grain yields to be obtained when compared to other management systems used